Temporal Trends in the Burden of Disease for Male Infertility from 1990 to 2021 in the BRICS - Xu R; Wang XJ; Lin QC; Zhuang YT; Zhou QY; Xu NF; Zheng DQ (Risk Management and Healthcare Policy, 2025)
Ran Xu,1 Xin-Jun Wang,2 Qing-Cheng Lin,3 Yan-Ting Zhuang,4 Qing-Ying Zhou,1 Nai-Fen Xu,1 Ding-Qin Zheng1 1Department of Urology, Pingyang Hospital of Wenzhou Medical University, Wenzhou, People’s Republic of China; 2Department of Urology, Zhongshan Hospital Xiamen University, School of Medicine, Xiamen University, Xiamen, People’s Republic of China; 3Department of Xiaojiang, Pingyang Hospital of Wenzhou Medical University, Wenzhou, People’s Republic of China; 4Department of Hepatobiliary and Pancreatic Surgery, Zhongshan Hospital Xiamen University, School of Medicine, Xiamen University, Xiamen, People’s Republic of ChinaCorrespondence: Ran Xu, Department of Urology, Pingyang Hospital of Wenzhou Medical University, No.555 Kunao Avenue, Wenzhou, Zhejiang, 325400, People’s Republic of China, Email xuran0817@163.comBackground: Over the past three decades, male infertility has become a significant burden on global public health. As an international organization with nearly half of the world’s population, BRICS plays a crucial role in global health. This study investigates the trend of male infertility burden in BRICS countries from 1990 to 2021, providing valuable information for prevention and treatment strategies.Methods: Data on male infertility in BRICS countries were obtained from the Global Burden of Disease database. Joinpoint regression, decomposition analysis, and prediction models were applied to analyze the data and assess the disease burden trends.Results: The global prevalence of male infertility has worsened significantly between 1990 and 2021, with projections indicating this trend will continue for the next 15 years. While this global trend is based on data from a range of countries, the results of this study specifically focus on the BRICS countries. In these countries, while China and the Russian Federation have had high prevalence rates, improvements were observed over the past 30 years. India and Brazil, though unable to control male infertility in this period, have managed to halt its worsening in recent years. South Africa experienced substantial fluctuations from 2001 to 2015, with further significant changes projected in the next 15 years.Conclusion: This study provides valuable insights into the evolving burden of male infertility in BRICS countries. It underscores the importance of targeted prevention and treatment strategies for these countries based on national and global trends.Keywords: male infertility, global burden of disease, joinpoint regression, brics, prevalence